Distorsi Kognitif dan Pola Pikir Disfungsional pada Remaja: Studi Kasus Layanan Kesehatan - Adilah Hasanah; Dyan Santi (Indonesian Journal Publisher, 2026)
This study aimed to describe the dynamics of cognitive distortions and dysfunctional thinking patterns in an adolescent receiving psychological services in a healthcare setting and to examine cognitive changes following a Cognitive Behavioral Therapy (CBT) based intervention. A mixed qualitative and quantitative approach with a single case study design was employed to obtain an in depth understanding of individual psychological changes before and after intervention. The participant was a sixteen year old female adolescent presenting emotional instability rigid negative thinking patterns and difficulties in family and school relationships. Data were collected through clinical interviews behavioral observations psychological testing and the Irrational Beliefs Inventory (IBI) administered as pre test and post test measures. The CBT based intervention was delivered in seven sessions focusing on psychoeducation identification of cognitive distortions understanding relationships between thoughts emotions and behaviors cognitive restructuring homework assignments and behavioral techniques for emotional regulation. Qualitative data were analyzed descriptively to capture changes in cognitive emotional dynamics while quantitative data from the IBI were used to evaluate intervention effectiveness. Results indicated a decrease in scores across all IBI dimensions after the intervention with notable reductions in rigidity excessive worrying problem avoidance and emotional irresponsibility. The total irrational belief score decreased by thirty seven points indicating a meaningful shift toward more adaptive and rational thinking patterns. Qualitative findings supported these results showing improved cognitive flexibility emotional awareness and coping strategies. Overall the findings demonstrate that CBT based cognitive restructuring is effective in reducing dysfunctional thinking patterns and improving emotional regulation in adolescents within healthcare settings. This study supports the application of CBT as an evidence based intervention for adolescents experiencing cognitive emotional difficulties and highlights its relevance for clinical psychological services in health care contexts.